COMPENSATION METHOD OF DIGITAL IMAGE DATA - FENG CHANG-YUNG; LIN HUNG-TSE; LIN YIH-MING (2006)
PROBLEM TO BE SOLVED: To provide a compensation method of digital image data for executing scanning operation for waiting for a stable required time and a compensation method of digital image data using software in a personal computer so as to save cost for implementing the compensation method. SOLUTION: The present invention relates to a compensation method for compensating digital image data generated from a scanning module of a scanner when the luminance of a lamp tube 202 is unstable. Several compensating gains are computed according to luminance values of a reference white plate so as to compensate the digital image data. The method of the present invention is implemented by software in a computer. COPYRIGHT: (C)2006,JPO&NCIPI